Moderating Effect of Access to Finance on the Relationship between Total Quality Management, Market Orientation and SMEs Performance: A Proposed Framework - Rogo, Halilu Bello; Shariff, Mohd Noor Mohd.; Hafeez, Muhammad Haroon (International Review of Management and Marketing, 2017)
This study proposed a framework for the moderating effect of Access to Finance (AF) on the relationship between Total Quality Management (TQM), Market Orientation (MO) and SMEs performance in Nigeria. However, relatively few studies have attempted to consider the relationship between Total Quality Management (TQM), Market Orientation (MO) and SMEs performance. The majority of the studies conducted on the relationship between the construct have presented different findings. In order to bridge the gap, a moderating effect of access to finance is introduce or proposed based on the suggestions of the literature. The study is significant to policy makers, government, regulators, and financial institutions on the need to provide access to finance to the real and potential entrepreneurs for SMEs development in Nigeria. In addition, the study will serve as additional literature to few studies on SMEs performance particularly in emerging economies like Nigeria that has not been explored. Keywords: Access to Finance, SMEs, TQM JEL Classifications: L26, L84